2013
DOI: 10.1073/pnas.1216893110
|View full text |Cite
|
Sign up to set email alerts
|

Particle shape enhances specificity of antibody-displaying nanoparticles

Abstract: Monoclonal antibodies are used in numerous therapeutic and diagnostic applications; however, their efficacy is contingent on specificity and avidity. Here, we show that presentation of antibodies on the surface of nonspherical particles enhances antibody specificity as well as avidity toward their targets. Using spherical, rod-, and disk-shaped polystyrene nano-and microparticles and trastuzumab as the targeting antibody, we studied specific and nonspecific uptake in three breast cancer cell lines: BT-474, SK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
366
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 476 publications
(384 citation statements)
references
References 44 publications
18
366
0
Order By: Relevance
“…One possible explanation is that for disc-and rod-shaped nanoparticles, larger size provides larger surface-contact areas for multivalent interactions with cell membranes (22,34). This effect may allow larger adhesion forces with particles and increase the probability of initiating cellular uptake.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One possible explanation is that for disc-and rod-shaped nanoparticles, larger size provides larger surface-contact areas for multivalent interactions with cell membranes (22,34). This effect may allow larger adhesion forces with particles and increase the probability of initiating cellular uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Between discoidal and rod-shaped nanoparticles of similar volume, nanodiscs were more efficiently internalized at all time points. Interestingly, Barua et al (22) reported that for nonspecific hydrophobic polystyrene particles, nanorods and nanodiscs have similar uptake in epithelial breast cancer cells. These differences could highlight the effect of hydrophobic versus hydrophilic surfaces as well as cell types evaluated and emphasize the importance of material composition in understanding nanoparticle-mediated intracellular delivery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron oxide nanoworms and gold nanorods have been shown to induce higher tumor accumulation (46,47), and gold nanorods have been shown to exhibit reduced macrophage clearance (48). Recent studies also showed the ability of rodshaped particles to bind specifically to cancer cells in vitro (49).…”
Section: Discussionmentioning
confidence: 99%